(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe knowledge of standard prevention of nursing at Hoa Binh general hospital in 2021. Subject and method: A cross-sectional model study was conducted from March 2021 to December 2021 with 284 nurses. Results: The percentage of hospital nurses who have correct knowledge about subjects applying standard prevention accounts for 90.1%; correct answer in the order of steps I the hand hygiene process is 78.2%; correct answer of using protective means accounted for a high rate of 93.7%; the percentage of hospital nurses who have knowledge of some contents in PNC is quite high at 83.8%. Hospitals need regular training and continuing education for nurses on standard precautions, with attention paid to knowledge of transmission routes in the hospital, hand hygiene, handling of linen and medical equipment. medical tools... Conclusion: In order to well implement standard prevention, medical examination and treatment facilities need to implement many synchronous solutions. Besides, it is necessary to train and provide enough knowledge on standard precautions for health workers.